Mechanistic analysis of ecological effects of graphene nanomaterials on plant ecosystems. (2nd April 2020) - Yang, Ying; Zhao, Yanqi; Wang, Mingshi; Meng, Hongqi; Ye, Zenghui
Abstract: As graphene is an emerging carbon nanomaterial, some studies have investigated the ecological effects of graphene‐based materials with generally focusing on physiological changes, enzyme activities, and oxidative stresses, but detailed mechanistic studies are actually lacking. Moreover, the results from previous studies were controversial in the context of ecological mechanisms, because material properties and organism species were quite different, and evaluation criterions were not uniform or reliable. Therefore, relative studies should be systematically initiated. This paper summarizes the research status between graphene related materials and soil–plant organisms, mainly discussing the detrimental influences on terrestrial biology from the perspectives of physiology, biochemistry, and gene expression. Moreover, probable toxicity mechanisms, impact factors, environmental application, and industrialization of graphene materials are also carefully discussed to provide scientific and theoretical basis.